(untitled) - Kazanjian, Kirk (Hoboken, N.J., 2005)
The book is divided into six parts, and fearures managers who specialize in a variety of styles and market sectors both in the United States and aboard. We begin by discussing the manager's background and how he or she got into the business. We then move into the Master's investment process and uncover the secrets of his or her success.
Keywords: Investment analysis,Investments,Stockbrokers,Phân tích đầu tư,Mô giới chứng khoán; United States,New York (State),New York (State)